Sistem Pendidikan Negara Jepang - Sepdiane, Falihah (Faktor : Jurnal Ilmiah Kependidikan, 2024)
This research uses literature review or research methods by collecting source materials and theories with relevant topics. This research has a background on technological and human developments that continue to change with the times so that the right steps are needed to be able to implement and develop the curriculum in the future. One of the nations in Asia with the highest educational standards is Japan, which also has a significant impact on global education. It is believed that by observing Japan's implementation and development of curriculum in high school classrooms, policies and curricula in emerging nations might be inspired by Japan. In this study, the author searched and collected several journals and then drew conclusions after being studied in depth through a detailed way so that there was a good final result and in accordance with what was expected. The study's findings demonstrate how the Japanese curriculum has evolved to attempt and change the attitudes and social conditions of Japanese society. These adjustments also take into account global events. Japan strives to develop quality education by developing the interests of students' talents in order to create a brilliant generation